2007
DOI: 10.1074/jbc.m708137200
|View full text |Cite
|
Sign up to set email alerts
|

Control of Phenotypic Plasticity of Smooth Muscle Cells by Bone Morphogenetic Protein Signaling through the Myocardin-related Transcription Factors

Abstract: In response to vascular injury, smooth muscle cells (SMCs) 2 exhibit a phenotypic change characterized by loss of contractility and abnormal proliferation, migration, and matrix secretion. This "synthetic" phenotype plays an active role in repair of the vascular damage. Upon resolution of the injury, local environmental signals within the vessel prompt SMCs to reacquire their "contractile" phenotype. SMC phenotype modulation contributes to the pathogenesis of numerous cardiovascular disorders, including PAH, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
168
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(180 citation statements)
references
References 74 publications
12
168
0
Order By: Relevance
“…Phenamil, benzamil, amiloride, and cyclosporine (CsA) were purchased from Sigma and solubilized in dimethyl sulfoxide (DMSO). The cells were treated under starvation conditions (0.2% FBS) as described previously (20).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenamil, benzamil, amiloride, and cyclosporine (CsA) were purchased from Sigma and solubilized in dimethyl sulfoxide (DMSO). The cells were treated under starvation conditions (0.2% FBS) as described previously (20).…”
Section: Methodsmentioning
confidence: 99%
“…In vSMCs, TGF-␤ and BMP have been shown to promote the contractile phenotype and inhibit switching to the synthetic phenotype (20). Both TGF-␤s and BMPs inhibit vSMC proliferation and migration and increase contractile vSMC gene expression (16,20,22). Loss-of-function mutations of the genes encoding receptors of TGF-␤s and BMPs have been linked to vascular disorders, such as idiopathic PAH (IPAH) and hereditary hemorrhagic telangiectasia (41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These VSMC phenotypic shifts are driven by a coordinated repression/activation of contractile markers SM22α, α‐SMA, and myocardin 28, 29. Notably, myocardin is a key specific transcriptional coactivator of α‐SMA 29…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was reported that activation of the RhoA-ROCK pathway by KCl through voltage-gated Ca 2ϩ channels upregulates the gene expression of myocardin and its target genes responsible for SM contractility in cultured vascular SM cells (SMCs). 10,11 Myocardin, a coactivator of serum response factor, 12 is necessary and sufficient for the vascular SMC contractile phenotype. 13,14 ATV, the most widely prescribed lipid-lowering drug, 15 was reported to inhibit the RhoA-ROCK pathway and attenuated the expression of myocardin and SM ␣-actin in human …”
mentioning
confidence: 99%